2015
DOI: 10.1007/s00289-015-1371-y
|View full text |Cite
|
Sign up to set email alerts
|

Electrical and mechanical characterization of a flexible conducting composite

Abstract: Composite films made of poly(vinylidene fluoride) (PVDF) and conducting particles of carbon black (CB) were prepared using a hot press. Using different volume fractions of CB filler, electrical properties of the samples were analyzed with current-voltage (I 9 V) measurements and impedance spectroscopy. To help the discussion, percolation theory and simulation circuits based on Colie diagrams were used. The percolation threshold was found at 3 vol% of CB. At these volume fractions of filler, scanning electron m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 21 publications
0
2
0
Order By: Relevance
“…Papers in the literature have demonstrated the good dispersion of CB and CNP‐based polymer composite. Deniz et al has observed that the CB particles presents good dispersion and interaction with the polyvinyl fluoride (PVDF), the fillers with spherical morphology showed to a small clusters formation separated by the PVDF matrix. Similar behavior has been observed by Arora et al which carried out a study of the chemical and physical properties of the acrylic resin/activated carbon composite.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Papers in the literature have demonstrated the good dispersion of CB and CNP‐based polymer composite. Deniz et al has observed that the CB particles presents good dispersion and interaction with the polyvinyl fluoride (PVDF), the fillers with spherical morphology showed to a small clusters formation separated by the PVDF matrix. Similar behavior has been observed by Arora et al which carried out a study of the chemical and physical properties of the acrylic resin/activated carbon composite.…”
Section: Resultsmentioning
confidence: 99%
“…It is crucial to examine the electrical properties of CPCs because of their immense potential for technological applications, for example, gas sensing, antistatic shielding, electronic and food packaging, and electromagnetic radiation shielding, as well as in the electronics and aerospace industries. Several studies have reported the preparation of CPCs from carbon black (CB), carbon nanotubes, carbon fibers, and activated carbon nanopowder (CNP), and the potential of a carbon‐based filler to improve the electrical properties of the insulator polymer matrix has been demonstrated . However, few studies have reported the electrical properties of CPCs based on biopolymers, such as castor‐oil polyurethane (PUR) with CB and CNP fillers.…”
Section: Introductionmentioning
confidence: 99%